Dendritic macromolecules as nano-scale drug carriers: Phase solubility, in vitro drug release, hemolysis and cytotoxicity study - Pravinkumar M. Patel; Rinkesh Patel; Devang Wadia; Rajni M. Patel (Asian Journal of Pharmaceutical Sciences, 2015)
Potential of nanoscale triazine based dendritic macromolecules G1, G2 and G3 as solubility enhancers of drug was investigated. Effect of pH, concentration and generation of synthesized dendritic macromolecules on solubility of ketoprofen was studied. G3 dendrimer was further exploited as carrier for sustained release. Ketoprofen was encapsulated by inclusion complex method and also characterized by Flourier Transform Infrared spectroscopy. Sustained release study of ketoprofen from ketoprofen loaded dendrimer was carried out and compared with free ketoprofen. Hemolytic potential and Cytotoxicity assay using A-549 lung cancer cell lines revealed that synthesized triazine based dendritic macromolecules having more potential that commercially available PAMAM dendrimer.